Behavioral Modification Enhances the Benefits from Structured Aerobic and Resistance Training - Dolezal, Brett A.; Boland, David M.; Neufeld, Eric V.; Martin, Jennifer L.; Cooper, Christopher B. (Sports Medicine International Open, 2019)
Behavioral modification (BM) is a strategy designed to sustain or restore well-being through effects such as enhanced relaxation, reduced stress, and improved sleep. Few studies have explored the role of BM delivered in the context of fitness programs for healthy adults. Thus, the purpose of this investigation was to examine whether BM combined with aerobic and resistance training programs would improve health and fitness measures more than the exercise training alone. Thirty-two healthy fitness club members (19 men) were randomized to receive a BM program (n=15) or an equal-attention (EA) control (n=17). BM consisted of twelve, 10-min education sessions between a trained fitness professional and the participant, coupled with weekly, individualized relaxation, stress reduction, and sleep improvement assignments. All participants engaged in 1 h of coached resistance training and remotely guided aerobic exercise thrice weekly for 12 weeks. Fitness measures (aerobic performance, body composition, muscle strength and endurance, lower-body power), sleep characteristics, and heart rate variability (HRV) were obtained at baseline and after the 12-week program. BM resulted in greater improvements in aerobic performance (increased maximum oxygen uptake, metabolic (lactate) threshold, and percent of maximum oxygen uptake at which metabolic threshold occurred), peak and average lower-body power, and body composition (decreased body fat percentage and fat mass) compared to EA. BM also positively influenced parasympathetic tone through increased High-frequency HRV. BM resulted in greater improvements in fitness measures, body composition, and heart rate variability compared with EA. These findings have intriguing implications regarding the role of BM in augmenting health and physical performance.
Keywords: behavioral modification; physical fitness; exercise; maximum oxygen uptake; heart rate variability; sleep intervention